THE EU’S ALTERNATIVE ROUTES TO ESCAPE THE JOINT DECISION TRAP: AN ASSESSMENT IN THE AFTERMATH OF THE 2015 REFUGEE CRISIS - Elif Cemre Beşgür (Ankara Avrupa Çalışmaları Dergisi)
After a failed attempt to reform the Dublin III Regulation, the European Commission presented the New Pact on Migration and Asylum in September 2020, aiming to abolish the Dublin Regulation. Although the policy-core remains unchanged, a consensus has not yet been reached on it. In this context, the research focuses on informal ways to cooperate for escaping what Scharpf (1998) calls “the joint decision trap”. Based on this theoretical premise, the article assesses whether exit mechanisms are adequate in resolving the deficiencies of the Common European Asylum System or not. The article argues that exit mechanisms only address the deficiencies to a limited extent. Therefore, they are far from compensating for the lack of reform and constituting a basis for long-term solutions.